China$1 (Bs Macroeconomic Outlooks Quarterly Forecast and Analysis Report, February 2013 - CMR of Xiamen University, .; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The research team makes the following forecasts: First, in 2013 China$1 (Bs growth will remain stable and reach 8.23 percent, an increase of 0.43 percentage points compared with the previous year; even though there is inflation pressure resulting from global monetary easing, severe inflation in China is unlikely to happen, and the consumer price index (CPI) will remain at 3.11 percent. Second, the growth of imports and exports will rebound, but the trade surplus will decrease further. Finally, the share of investment in GDP will continue to be high in the short term as urbanization promotes the growth of fixed assets investment, though higher per capita incomes will result in high and steady consumption.s
Review of China$1 (Bs Macroeconomic Performance in 2012 -- Forecast of China$1 (Bs Macroeconomic Outlook for 2013-2014 -- Policy Simulations -- Policy Implications and Suggestions -- Comments and Discussions.s
Keywords: Economics; Endogenous growth (Economics).; Macroeconomics; Finance; Economics/Management Science; Macroeconomics/Monetary Economics; Economic Growth; Public Finance & Economics